Neural Networks Applied to the Control of a Four-Wire Shunt Active Power Filter - Marcelo G. Villalva; Ernesto Ruppert Filho (Eletrônica de Potência)
This paper presents a four-wire shunt active power filter fully controlled with neural networks. The paper is centered on a current compensation method based on adaptive linear elements (adalines), which are powerful and easy-to-use neural networks. The reader will find here an introduction about these networks, an explanatory section about the achievement of Fourier series with adalines, and the full description of an adaline-based selective current compensator. The paper also brings a discussion about the use of a feedforward neural network in the current controller of the active filter, as well as simulation and experimental results obtained with a prototype of a shunt active power filter.